Politics of transit in Turkey :|analysis of bilateral energy relations with Russia and the European Union - Şahin, Samed. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
Turkey is a strategic transit country located on the routes of energy flow between the leading supplier and the largest market in the region, Russia and the European Union (EU). Taking advantage of this geopolitical virtue, it aims to serve as a hub-and spoke network that would transfer Russian gas to Europe, which is also vital to meet its domestic energy needs. Being both an aspiring energy hub and an import dependent country, the long-term stability in bilateral relations with market actors is a must for Turkey. However, ironically, Turkey’s bilateral relations with Russia and the EU have been rather chaotic and characterized by political rifts and crises in recent years. Nevertheless, Turkey has been fairly able to maintain its energy security and develop even more ambitious energy policies in the last two decades. That begs the question: how does Turkey maintain the energy cooperation with regional energy actors even though its bilateral relations are mostly problematic? I argue that Turkey has maintained energy cooperation thanks to the compartmentalization strategy, which allows Turkey to isolate the cooperation areas from conflicts. The case study analysis of Turkey’s bilateral relations with Russia and the EU shows that compartmentalization would allow Turkey to 1) secure its long-term economic interests; 2) bypass regional, ideational, and structural conflicts; and 3) conduct quick reconciliation in the aftermath of crises. The comparison of Russia and the EU cases shows that compartmentalization would produce mostly similar outcomes, if not identical.
Keywords: Energy policy -- Russia.; Energy policy -- Europe.; Europe -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- Europe.; Turkey -- Strategic aspects.